1999
DOI: 10.1111/j.1744-7348.1999.tb00868.x
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action of fosthiazate used for the control of the potato cyst nematode Globodera pallida

Abstract: Fosthiazate (Nemathorin 1OG Ishihara Sangyo Kaisha Ltd, Japan) is a new nematicide approved for use on potatoes Solanum tuberosum L. in the UK for the control of the potato cyst nematodes Globodera rostochiensis (Woll). Skarbilovich and G. pallida (Stone). Fosthiazate delayed and suppressed hatch of the potato cyst nematode Globodera pallida in both in vitro laboratory tests and a glasshouse pot experiment. In vitro hatch was temporarily inhibited by fosthiazate concentrations above 0.09 pg ml-I and increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 17 publications
5
18
0
Order By: Relevance
“…Additionally, treatment of cysts with fosthiazate does not permanently inhibit hatching. It only slows down the hatching rate and this is in agreement with the findings by Woods et al (1999) on potato cyst nematodes. While as inhibition of acetylcholinesterase by oxime carbamates like aldicarb and oxamyl is reversible, the process is thought to be irreversible with fosthiazate (Richard, 1960;Yu et al, 1972) and this was supported by the limited number of hatched infective juveniles in comparison to the control.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Additionally, treatment of cysts with fosthiazate does not permanently inhibit hatching. It only slows down the hatching rate and this is in agreement with the findings by Woods et al (1999) on potato cyst nematodes. While as inhibition of acetylcholinesterase by oxime carbamates like aldicarb and oxamyl is reversible, the process is thought to be irreversible with fosthiazate (Richard, 1960;Yu et al, 1972) and this was supported by the limited number of hatched infective juveniles in comparison to the control.…”
Section: Discussionsupporting
confidence: 81%
“…Fosthiazate is an acetylcholinesterase inhibitor that negatively affects nematode hatching and movement (Woods et al, 1999). Thus, this could explain the slow progress of hatching compared to the control in our experiment.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Fosthiazate and cadusafos are used in Japan and other countries. Their high levels of activity toward plant parasitic nematodes have already been reported 12,22,25,44) .…”
Section: Contact Actionmentioning
confidence: 91%
“…Studies have shown that fosthiazate exhibits efficacy in field plots similar to other non-fumigant nematicides against a wide range of plant parasitic nematodes (Hafez and Sundararaj, 2006;Kimpinski et al, 1997;Woods et al, 1999). Following the ban on the use of other organophosphorus nematicides with high toxicity and methyl bromide on vegetables due to their adverse effect on the environment and human health, fosthiazate, whose use has been rising exponentially in recent years, is considered to be one of the most efficient nematicides in controlling root-knot nematodes in protected crops (Giannakou et al, 2005).…”
Section: Introductionmentioning
confidence: 99%